2023
DOI: 10.1002/alr.23225
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution exposure is associated with rhinitis in older US adults via specific immune mechanisms

Abstract: BackgroundPathophysiology of rhinitis in older adults is largely unknown. We tested whether air pollution is associated with this condition and how immune mechanisms may play a role in this relationship.MethodsWe analyzed cross‐sectional data from the National Social Life, Health, and Aging Project, a nationally representative study of older adults born between 1920 and 1947. Particulate matter ≤2.5 μm (PM2.5) air pollution exposure estimates were generated using validated spatiotemporal models. Presence of rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…We read with great interest the recent research 1 exploring the intricate relationship between air pollution exposure and rhinitis in older adults. The study sheds light on the specific immune mechanisms through which air pollution might contribute to the development of this condition.…”
Section: Letter To the Editor Regarding "Air Pollution Exposure Is As...mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the recent research 1 exploring the intricate relationship between air pollution exposure and rhinitis in older adults. The study sheds light on the specific immune mechanisms through which air pollution might contribute to the development of this condition.…”
Section: Letter To the Editor Regarding "Air Pollution Exposure Is As...mentioning
confidence: 99%
“…Natural Science Foundation of Xinjiang Uygur Autonomous Region, Grant No. : 2020D03009 Ling Tie MD 1 Guangjian Jiang MD 2…”
Section: F U N D I N G I N F O R M At I O Nmentioning
confidence: 99%
“…To the Editor, I read with great interest the recent article by Scussiatto et al 1 The authors evaluated the hypothesis that air pollution is associated with rhinitis. They found that long-term exposure to particulate matter ≤2.5 µm (PM 2.5 ) was associated with rhinitis, and elevated interleukin (IL)-3, IL-12, and interferon-γ levels could be involved in the immune pathways in this association.…”
mentioning
confidence: 99%